Molecular survey of Bartonella spp. and haemoplasmas in American minks (Neovison vison) - Sepúlveda-García, Paulina; Raffo, Eduardo; Medina-Vogel, Gonzalo; Muñoz, Francisco; Muñoz, Pamela; Alabí, Amir; Navarrete-Talloni, Maria Jose; Gonçalves, Luiz Ricardo [UNESP]; Califre de Mello, Victória Valente [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP]; Bittencourt, Pedro; et al. (Hindawi, 2020)
The aim of this study was to perform a molecular survey and characterize Bartonella spp. and haemotropic Mycoplasma (haemoplasmas) in invasive American minks (Neovison vison) from Southern Chile. Additionally, we addressed risk factors for positivity in both groups of agents. Blood and/or tissue samples from 246 minks were analysed by qPCR targeting the nuoG gene for Bartonella spp. and conventional (c)PCR for 16S rRNA for haemotropic Mycoplasma spp. nuoG qPCR-positive Bartonella spp. samples were submitted to cPCR assays (ITS, ribC, gltA, rpoB, pap-31 and ftsZ genes) to perform phylogenetic inferences. Haemotropic Mycoplasma spp. 16S-positive samples were further amplified by cPCR targeting RNaseP gene (160–210 bp) and by two overlapping 16S rRNA cPCR assays to amplify a larger portion of the gene (1,200bp) for phylogenetics. Bartonella DNA was detected in 8.9% of minks (22/246). Out of 22 nuoG qPCR-positive samples, one and two showed positive results in cPCR assays based on ITS and ribC, respectively. Consistent sequencing results were obtained for only one ITS sample (464 bp sequence), which shared 99.6% identity with B. clarridgeiae. Two per cent of minks (5/246) were positive for 16S rRNA haemotropic Mycoplasma-cPCR assay. Two concatenated sequences of 16S rRNA (1,176 and 1,230 bp) were obtained: one sample shared 97.87% identity with haemotropic Mycoplasma sp. from a wild rodent, and the other 96.49% identity with ‘Candidatus Mycoplasma haematoparvum’ from a dog. All BLAST results were supported by phylogenetic analysis. One haemoplasma RNase P sequence shared 94.86% identity with Mycoplasma haemofelis from a cat. No risk factors for PCR positivity were identified. In a nutshell, Bartonella clarridgeiae and a potentially novel haemoplasma closely related to haemoplasmas previously reported in rodents, dogs, domestic and wild cats were described for the first time in American minks.
Keywords: Bartonellosis; Chile; haemotropic Mycoplasma; mustelids; PCR; South America